Healthcare professionals' perceptions of using a digital patient educational programme as part of cardiac rehabilitation in patients with coronary artery disease - a qualitative study - Jenny Danielsbacka; Caroline Feldthusen; Maria Bäck (BMC, 2023)
Abstract Background Participation in cardiac rehabilitation in patients with coronary artery disease (CAD) remains underutilised. Digital educational programmes, as part of cardiac rehabilitation, are emerging as a means of increasing accessibility, but healthcare professionals' perceptions of implementing and using these programmes are not known. The aim of the study was therefore to explore healthcare professionals ̓ perceptions and experiences of implementing and using a digital patient educational programme (DPE) as part of cardiac rehabilitation after acute CAD. Methods Individual semi-structured interviews were performed with 12 nurses and physiotherapists, ten women with a median age of 49.5 (min 37- max 59) years, with experience of using the DPE as part of a phase II cardiac rehabilitation programme in Region Västra Götaland, Sweden. The interviews were transcribed verbatim and analysed with inductive content analysis according to Graneheim and Lundman. Results An overall theme was identified throughout the unit of analysis: "Digital patient education - a complement yet not a replacement". Within this theme, three main categories were identified: "Finding ways that make implementation work", "Accessibility to information for confident and involved patients" and "Reaching one another in a digital world". Each main category contains a number of sub-categories. Conclusions This study adds new knowledge on healthcare professionals' perceptions of a digital patient educational programme as a valuable and accessible alternative to centre-based education programmes as part of cardiac rehabilitation for patients with CAD. The participants highlighted the factors necessary for a successful implementation, such as support through the process and sufficient time from the employer to learn the system and to create new routines in daily practice. Future research is needed to further understand the impact of digital education systems in the secondary prevention of CAD. Ultimately, hybrid models, where the choice of delivery depends on the preferences of the individual patient, would be the optimal model of care for the future.